2020
DOI: 10.3390/su12062285
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the Types and Impact of Service Provider’s Responses to Online Negative Reviews in the Sharing Economy: Evidence from B&Bs in China

Abstract: Online consumer complaints are closely related to business reputation and elicit managers' persistent efforts. However, service providers in the sharing economy (SE) lack the skills to communicate with consumers because most are informal or nonprofessional property owners. This research aims to examine the relationship between service providers' responses and prospective consumers' perceived helpfulness in the SE by using bed and breakfasts (B&B) as the sample. Response length and voice are adopted to measure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 78 publications
0
8
0
Order By: Relevance
“…Intention refers to “the degree to which a person has formulated conscious plans to perform or not perform some specified future behavior” (Warshaw and Davis, 1985, p. 214). For consumers to form an actual intention to use a product or service, they first have to form a positive image of that product or service (Han and Hyun, 2017; Hwang and Kim, 2019; Liu et al , 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Intention refers to “the degree to which a person has formulated conscious plans to perform or not perform some specified future behavior” (Warshaw and Davis, 1985, p. 214). For consumers to form an actual intention to use a product or service, they first have to form a positive image of that product or service (Han and Hyun, 2017; Hwang and Kim, 2019; Liu et al , 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Values in this study mean the extent to which a person has a favorable opinion and judgment of the sharing economy and what it represents [82,87,88]. Regarding consequences, it has been specifically proven that values related to sustainability and solidarity affect consumers' preferences and expectations associated with Electronic Word of Mouth (eWOM) [89][90][91][92]. EWOM is defined as the information exchanges, evaluations and comments made through sites [93].…”
Section: The Importance Of Valuesmentioning
confidence: 99%
“…In addition, response length is used to assess the quality of a hotels' response to an online complaint. Previous research (Liu & Ji, 2019;Liu et al, 2020) has shown that the length of a hotels' response in online review substantially impacts 'customers' perceived helpfulness. According to this research, hotels should be aware of good and bad internet reviews and take proactive measures to minimise customer complaints while fostering an upbeat environment.…”
Section: 3) the Length Of The Hotels' Response To Negative Reviews An...mentioning
confidence: 99%